Assessment of Factors Associated with Household Expenditure in Gajuri Rural Municipality, Dhading, Nepal - Acharya, Krishna Prasad (Nepal Journal of Multidisciplinary Research, 2024)
Background: Household expenditure is the total amount of money spent by a household for food, cloth, shelter, education, health, transportation, sanitation, entertainment, and so on. The objective of this study is to identify the significant factors affecting household expenditure in the rural area from the collected 897 primary data from the Gajuri Municipality in December, 2022. Methods: Stratified random sampling method was used for the data collection and the secondary data was used from the Sahabhagitamulak Gajuri Bikas Guru Yojana, 2074. Ordinary least square regression method was used to analyze the data. Results: The result of this study shows that the size of the household (β = 0.023, p < 0.001), gender of the household head (β = 0.059, p=0.003), income of the household (β = 0.093, p < 0.001), access to internet in the house (β = -0.191, p < 0.001), and the access to the television in the house (β = -0.090, p < 0.001) were found important in determining household expenditure in this municipality. Conclusion: From this study, it can be found that the size of the household, gender of the household head, income of the household, access to the internet in the house and access to the television in the house are strongly associated with household expenditure instead of literacy status of household head, remittance receiving status of household, and age of the household head due to the contemporary development and advancement in the society. This study could help policy makers assess factors determining household expenditure and develop plans for Gajuri Rural Municipality. Novelty: In underdeveloped countries, it is difficult to determine exactly what housing costs are especially in rural areas. This is because uneducated landowners do not account for the consumption of agricultural produce and the expenditure incurred in it.